Feeding behavior during adaptation phase of beef cattle in feedlot reducing the use of conventional growth promoters - Oliveira, A. P.; Romanzini, E. P. [UNESP]; Leite, R. G. [UNESP]; Delevatti, L. M. [UNESP]; Fernandes, L. B.; D'Aurea, A. P.; Reis, R. A. [UNESP]; Chizzotti, M. L. (Wageningen Acad Publ, 2019)
The aim this study was evaluate associations between feeding behavior and animal performance of feedlot cattle. Treatments were Control (CN - 24.4 mg/kg dry matter [DM] of monensin + 19.5 mg/kg DM of virginiamycin) and Standard (ST - 584.8 mg/kg DM of Fator P (R) + 12.2 mg/kg DM of monensin). Nellore young bulls (n=48), weighing 394.1 +/- 6.3 kg, were used, divided into twelve collective pens. Multivariate analysis by factor method using STATISTICA Multivariate Exploratory Techniques and General Linear Model analysis using STATISTICA Advanced Linear/Nonlinear Models, were developed. Considering total variability (63.65%), the Factor 1 had 35.19%), while Factor 2 had 28.46%. For Factor 1 there was association among average daily gain, feed efficiency and idle time, which were negatively associated to feed conversion and feeding time. There were no differences between treatments (P=0.28) for Factor 1. For Factor 2, there was a biological association between dry matter intake (DMI) and ruminating time (RT) which were negatively associate to nutrient apparent digestibility. There were differences between treatments for Factor 2 (P=0.01). Animals fed CN decreased DMI, reducing RT and increasing nutrient apparent digestibility compared to animals fed ST. These results can be due to the natural additive associated to a half of dosage of monensin not affect the DMI. There are biological association between feeding behavior and animal performance during adaptation phase of beef cattle in feedlot systems.
Keywords: dry matter intake; monensin; multivariate analysis